High-Speed All-Optical Encoder and Comparator at 120 Gb/s Using a Carrier Reservoir Semiconductor Optical Amplifier - Amer Kotb; Kyriakos E. Zoiros (Nanomaterials)
All-optical encoders and comparators are essential components for high-speed optical computing, enabling ultra-fast data processing with minimal latency and low power consumption. This paper presents a numerical analysis of an all-optical encoder and comparator architecture operating at 120 Gb/s, based on carrier reservoir semiconductor optical amplifier-assisted Mach–Zehnder interferometers (CR-SOA-MZIs). Building upon our previous work on all-optical arithmetic circuits, this study extends the application of CR-SOA-MZI structures to implement five key logic operations between two input signals (A and B): <semantics><mover>A¯</mover>B</semantics>, <semantics>A<mover>B¯</mover></semantics>, AB (AND), <semantics><mover>A¯</mover> <mover>B¯</mover></semantics> (NOR), and AB + <semantics><mover>A¯</mover> <mover>B¯</mover></semantics> (XNOR). The performance of these logic gates is evaluated using the quality factor (QF), yielding values of 17.56, 17.04, 19.05, 10.95, and 8.33, respectively. We investigate the impact of critical design parameters on the accuracy and stability of the logic outputs, confirming the feasibility of high-speed operation with robust signal integrity. These results support the viability of CR-SOA-MZI-based configurations for future all-optical logic circuits, offering promising potential for advanced optical computing and next-generation photonic information processing systems.